Kepastian Hukum sebagai Jaminan Perlindungan Hak Penggugat dalam Kasus Wanprestasi Jual Beli Properti - Benedict Philip Christian; Gunawan Djajaputera (Jurnal Hukum Lex Generalis, 2024)
This study aims to analyze legal certainty as a guarantee of protection for the plaintiff’s righs in cases of breach of contact in property sales transactions. Breach of contract in property sales often involves diputes that can cause financial and legal harm to the plaintiff. Therefore, it is important to undertstand how legal certainty can play a role as a mechanism for protecting the plaintiff’s rights in the resolution of such disputes. This research examines the application of positive law, particularly regulations related to property sales and breach of contract, as well as legal remedies available to the aggrieved party. The approach used in this research is a normative approach, analyzing laws, regulations, and relevant jurisprudence. The findsings of the study show that although there is a clear legal framewrok governing the rights of the study show that although there is a clear legal framwork governing the rights and obligations of parties in property sales transactions, there are still gaps in the implementation of legal certainty that may hinder the protection of the plaintiff’s rights. Therefpre, there is a need for legal reforms and more assertive law enforcement to ensure that legal certainty can provide optimal protection for the aggrieved party in breach of contract cases.